A Call to Action: Improving the Surgical Training Experience for Residents Underrepresented in Medicine. Issue 2 (19th February 2023) - Liu, Timothy P.; Wang, Andrew; Sheppard, William L.; Stavrakis, Alexandra I.; Hines, Oscar J.; McIntosh, David
Abstract :